2021
DOI: 10.1186/s12885-021-08800-w
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of cigarette smoking, DNA methyltransferase 3B genetic polymorphism, and DNA damage on lung cancer

Abstract: Background Smoking increases DNA methylation and DNA damage, and DNA damage acts as a vital cause of tumor development. The DNA methyltransferase 3B (DNMT3B) enhances promoter activity and methylation of tumor suppressor genes. Tea polyphenols may inhibit DNMT activity. We designed a case-control study to evaluate the combined effects of smoking, green tea consumption, DNMT3B − 149 polymorphism, and DNA damage on lung cancer occurrence. Methods Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…CS is implicated in inducing hypermethylation mechanism via increasing the expression of DNA methyl transferase enzymes (DNMTs) [ 42 , 43 ]. The possible mechanism could be through DNA damage on DNMT3b which occurs as a result of the existences of carcinogens content in CS including arsenic, formaldehyde, and nitrosamines [ 44 ], leading to a transition from C to T that is located on the promoter 149 bp away from the transcription start site; it was revealed that nonsmokers harbor DNMT3b –149 CT genotype while smokers contain DNMT3b –149 TT genotype [ 42 ]. Consequently, an increase of DNMT3b activity is observed, causing an establishment of de novo methylation of CpG on some tumor suppressor genes [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…CS is implicated in inducing hypermethylation mechanism via increasing the expression of DNA methyl transferase enzymes (DNMTs) [ 42 , 43 ]. The possible mechanism could be through DNA damage on DNMT3b which occurs as a result of the existences of carcinogens content in CS including arsenic, formaldehyde, and nitrosamines [ 44 ], leading to a transition from C to T that is located on the promoter 149 bp away from the transcription start site; it was revealed that nonsmokers harbor DNMT3b –149 CT genotype while smokers contain DNMT3b –149 TT genotype [ 42 ]. Consequently, an increase of DNMT3b activity is observed, causing an establishment of de novo methylation of CpG on some tumor suppressor genes [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Sunberg et al [7] found a significant increase in P16 expression among smokers compared to nonsmokers in oral squamous cell carcinoma. Similarly, Liu et al [11] reported a positive correlation between smoking and p53 overexpression in oral leukoplakia [12,13].…”
Section: Introductionmentioning
confidence: 82%
“…For example, Sunberg et al [ 7 ] found a significant increase in P16 expression among smokers compared to nonsmokers in oral squamous cell carcinoma. Similarly, Liu et al [ 11 ] reported a positive correlation between smoking and p53 overexpression in oral leukoplakia [ 12 , 13 ]. The current study investigated the cellular alterations and the immunohistochemical expression of p53 and p16 in the oral mucosa among smokers in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 96%